Penentuan Lokasi Tempat Pembuangan Akhir Sampah Kecamatan Kendawangan Kiri Menggunakan Simple Additive Weighting - Arindika, Utin Syarifah; Utami, Putri Yuli; Istikoma, Istikoma (STMIK Banjarbaru, 2024)
The waste management issue in Kendawangan Kiri District is currently facing difficulties in finding a suitable location for the Final Disposal Site (TPA). This research aims to determine the location of the waste Final Disposal Site in Kendawangan Kiri District using the Simple Additive Weighting (SAW) method. The SAW method is used to determine alternatives, criteria, costs and benefits, assessment criteria, provide suitability ratings, normalize weights and decision matrices, normalize matrices, ranking, and analyze questionnaire results using SPSS. The web design implementation includes login displays, dashboards, alternatives, criteria weights, matrices, and preference values. System testing is conducted through black box testing to ensure system compliance with analysis and design. The SAW data processing results show that the alternative with the highest percentage is Kendawangan Kiri Village with a value of 0.87%, followed by Banjarsari Village 0.67%, and Mekar Utama Village 0.55%.Â